Efeitos do uso do desenvolvimento orientado por testes em conjunto com critérios de teste na indústria de software ágil - Matos, Altieres de (2020)
Context: The impact of adopting test criteria on software development using Test Driven Development (TDD) is unclear. There is insufficient evidence to define the impact of these new activities on the productivity and effective quality of the software. With the increase in the interest of professionals in automation of test cases, there are factors that limit the adoption of TDD in the software industry. Goal: Propose the adoption of TDD in conjunction with testing criteria, providing a tool for analyzing the compliance of the TDD process, analyzing the effects generated in its adoption and evaluating the existence of the increase in the quality of products in software industries inserted in the agile context with an iterative model. Method: In this study, a case study was defined involving information technology professionals in a software industry located in northwestern Paraná, in order to answer the research question: There are improvement effects in the software development during the adoption of Test Driven Development (TDD) and test criteria? Outcomes: We produced the Butterfly tool, an extension to the IDE Eclipse, responsible for measuring the compliance of the TDD process during the software development cycle. With the execution of the case study, we achieved evidence regarding the adoption of TDD, improving the quality of the software product and impacting the work effort. We materialized an experimental package derived from the case study carried out, providing that other researchers can carry out other studies in similar scenarios, collecting new evidence. Conclusion: We conclude that there are signs of improvement effects on software development during the adoption of TDD in conjunction with criteria, based on the evidence collected on the conformity of the development process and the quality of the software developed. Regarding the compliance of the TDD process, we had a reduction in the percentage of use of TDD, but we had an increase in the percentage of coverage of the functional test requirements. Regarding the quality of the software, we had a reduction in the number of code smells and defects, but there was a reduction in the percentage of line coverage and mutation.